Association analysis of the transforming growth factor factor-β2 gene with growth performance in Kedu chickens - Akramullah, M.; Kurnianto, E.; Lestari, D. A.; Setiatin, E. T.; Palupi, D. Y.; Anjani, Y. N.; Dewi, G. P.; Setiaji, A. (Diponegoro University, 2026)
The Transforming Growth Factor-β2 (TGF-β2) gene is one of the cytokine genes that plays an important role in regulating growth processes and disease resistance. This study aimed to analyze the association between the TGF-β2 gene and growth performance in Kedu chickens. A total of 130 Kedu chickens, consisting of 72 males and 58 females, were observed for 10 weeks. Growth parameters measured included body weight, feed intake, body weight gain, and feed conversion ratio. Identifica-tion of the single nucleotide polymorphism (SNP) in the TGF-β2 gene was performed using the PCR-RFLP method. The association analysis between the g.640 T>C SNP polymorphism of the TGF-β2 gene and growth performance was conducted using analysis of variance under a General Linear Model (GLM). The results showed that the g.640 T>C SNP of the TGF-β2 gene was polymorphic and not in Hardy–Weinberg equilibrium. The TT genotype exhibited better growth performance (body weight gain, feed intake, and feed conversion ratio) than the CC genotype, particularly at 10 weeks of age in both female and unsexed chickens.